Structure-guided mutagenesis reveals a hierarchical mechanism of Parkin activation - Matthew Y. Tang; Marta Vranas; Andrea I. Krahn; Shayal Pundlik; Jean- François Trempe; Edward A. Fon (Nature Communications, 2017)
Parkin and PINK1 are involved in damaged mitochondria clearance; however the sequence of events of Parkin activation is not clear. Here, the authors show that binding to phospho-ubiquitin on mitochondria enables Parkin phosphorylation, which allows Repressor Element of Parkin removal, E3 ligase activation and mitophagy.